MUTU BIJI KAKAO LINDAK PADA BERBAGAI LAMA WAKTU FERMENTASI - Nursalam, Nursalam (AgriSains, 2005)
The purposes of the research were to know the quality of cacao bulk on various time depth of fermentation. It was done in Rahmat of Palolo Sub-District, Donggala District.        The Research was set up in Randomized Block Design with 6 treatments and 3 replications. The treatments were ; (L0) without fermentation, (L1) 2 days, (L2) 4 days, (L3) 6 days, (L4)        8 days and (L5) 10 days fermentation time depth. The Result indicated that treatment fermentation time depth had effect on quality of kakao bulk and 6 days fermentation showed the best result from all of the treatments.  Even thought on the statistic, that treatment had little differ with 8 days fermentation. Key words: Quality, cacao, fermentation, time depth